Endophytic fungus isolated from Zingiber officinale Linn. var. rubrum as a source of antimicrobial compounds - Dian Handayani, Hardieta Citra Sari, Elin Julianti, Muh. Ade Artasasta (Journal of Applied Pharmaceutical Science, 2023)
In Indonesia, red ginger (Zingiber officinale Linn. var. rubrum) is an essential traditional medicine used to treat various ailments. Red ginger plants may have an endophytic fungus capable of producing several bioactive chemicals. This research aimed to identify endophytic fungi and evaluate their antimicrobial efficacy. The fungal strains were isolated from red ginger leaves, stems, and rhizomes by direct planting and pour methods using fungus culture medium and cultivated on rice medium. In the secondary metabolite extraction process, ethyl acetate (EtOAc) is used as a solvent. The agar diffusion procedure examined the EtOAc extract for antibacterial activity against Staphylococcus aureus, Escherichia coli, and Candida albicans. This study succeeded in isolating 10 fungal strains. The result of antimicrobial screening revealed that the fungal strain JMR4 has a high ability to suppress the development of pathogenic bacteria S. aureus and E. coli, with an inhibition zone of 14.38 ± 1.34 and 16.88 ± 0.69 mm, respectively. The fungus was later identified using the molecular approach, which stated that this fungus is Aspergillus terreus. This research demonstrates that endophytic fungus on red ginger plants may synthesize antibacterial substances crucial for developing novel antibiotics.